Fryderyk Chopin w literaturze francuskiej: od figury romantycznej do ikony popkultury - Malinowski, Wiesław Mateusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The reception of Chopin and his music in French literature follows the rhythm of the changes in the European intellectual and aesthetic climates. George Sand recorded in her memoirs the image of a romantic genius par excellence, a dark, torn and complicated soul. The decadent and symbolist poetry, best exemplified by Maurice Rollinat, presents a portrait of a blood-spitting neurasthenic, a soulmate of the poet. Marcel Proust paints the image of an elegant dandy and exquisite artist, while the first part of the twentieth century is dominated by the neoromantic vision of Chopin as a great Polish patriot; this theme is perfectly illustrated by the poems of Anna de Noailles and Edmond Rostand. André Gide presents a radically new view of Chopin’s music, seeing the Polish composer as a neoclassicist pianist. Contemporary literature and art go on to dress Chopin in jeans, eagerly turning him into a mass culture hero.